Innovation of multi fiber coupling of fused silica fiber - Irawan, Dedi (2011)
This paper presents the estimation of normalized coupling power among multi coupled fibers. Power transfer between the fibers has been determined based on coupled mode theory using Transfer Matrix Method. Theoretical calculation has shown that power in a fiber is no longer to be completely transferred to other M fibers (M>3). This is caused by the coupling coefficient between them. The coupled power or coupling ratio among M fibers can be controlled by maintaining the coupling parameters. Experimentally, the change of coupling ratio is investigated, and theoretically by applying dc voltage to the coupling region of fiber coupler. In three dimension, the coupling power distribution shows that strongly depends on the coupling coefficient and coupling length. However, by knowing the coupling power parameters, the fiber coupler of MXN fibers are easier to be fabricated and more applicable in optical network system.